Actin cytoskeleton dynamics linked to synovial fibroblast activation as a novel pathogenic principle in TNF-driven arthritis. (12th October 2007) - Vasilopoulos, Y; Gkretsi, V; Armaka, M; Aidinis, V; Kollias, G
Abstract : Rheumatoid arthritis is a chronic inflammatory disorder whose origin of defect has been the subject of extensive research during the past few decades. While a number of immune and non-immune cell types participate in the development of chronic destructive inflammation in the arthritic joint, synovial fibroblasts have emerged as key effector cells capable of modulating both joint destruction and propagation of inflammation. Ample evidence of aberrant changes in the morphology and biochemical behaviour of rheumatoid arthritis synovial fibroblasts have established the tissue evading and "transformed" character of this cell type. We have recently demonstrated that actin cytoskeletal rearrangements determine the pathogenic activation of synovial fibroblasts in modelled TNF-mediated arthritis, a finding correlating with similar gene expression changes which we observed in human rheumatoid arthritis synovial fibroblasts. Here, we show that pharmacological inhibition of actin cytoskeleton dynamics alters potential pathogenic properties of the arthritogenic synovial fibroblast, such as proliferation, migration and resistance to apoptosis, indicating novel opportunities for therapeutic intervention in arthritis. Recent advances in this field of research are reviewed and discussed.